Satisfaction Analysis of Bus Stop Accessibility: A Case Study of Batam Center - Steven Steven; Andri Irfan Rifai (LEADER: Civil Engineering and Architecture Journal, 2023)
Accessibility of public transport has always been a major issue in urban transportation. Batam City as one of the fastest-growing cities in Indonesia undoubtedly facing a rapid increase in transport needs. Despite its importance, the assessment of bus stop accessibility in Batam City is still less than enough. Batam Center as one of the major districts in Batam City is chosen as the case study area. To assess current accessibility, a questionnaire is distributed online and offline which results in 50 respondents. The data is then interpreted using IPA method. Results show that there is a -1.32 gap from performance to importance. Furthermore, distributing to the matrices shows that most of the critical aspects in accessibility fall into Quadrant B (high importance, low performance). This means the bus stops accessibility in Batam Center is still not satisfactory.